A holographic mobile-based application for practicing pronunciation of basic English vocabulary for Spanish speaking children. Issue 124 (April 2019) - Cerezo, Rebeca; Calderón, Vicente; Romero, Cristóbal
Highlights: A Holographic mobile-based application is used to practice the pronunciation of basic English vocabulary words. A funny 3D holographic robot interacts as virtual teacher in charge of practicing. An experiment with 70 Spanish pre-school children has been carried out. Results shown a significant impact on the children's motivation and performance. Abstract: This paper describes a holographic mobile-based application designed to help Spanish-speaking children to practice the pronunciation of basic English vocabulary words. The mastery of vocabulary is a fundamental step when learning a language but is often perceived as boring. Producing the correct pronunciation is frequently regarded as the most difficult and complex skill for new learners of English. In order to address these problems this research takes advantage of the power of multi-channel stimuli (sound, image and interaction) in a mobile-based hologram application in order to motivate students and improve their experience of practicing. We adapted the prize-winning HolograFX game and developed a new mobile application to help practice English pronunciation. A 3D holographic robot that acts as a virtual teacher interacts via voice with the children. To test the tool we carried out an experiment with 70 Spanish pre-school children divided into three classes, the control group using traditional methods such as images in books and on the blackboard, and two experimental groups using our drills and practice software. One experimental group used the mobile application without the holographic game and the other experimental group used the application with the holographic game. We performed pre-test and post-test performance assessments, a satisfaction survey and emotion analysis. The results are very promising. They show that the use of the holographic mobile-based application had a significant impact on the children's motivation. It also improved their performance compared to traditional methods used in the classroom.